Photochemical Insights into Light: Responsive Heterocyclic Compounds - Rizwan Arif (International Journal of Photochemistry and Photochemical Research, 2024)
eterocyclic compounds are significant in a wide range of chemical fields. They are crucial components of the structural makeup of bioactive substances. Such compounds can be conveniently transformed through photochemical processes. Chemical reagents are rarely utilized. It is possible for members of one compound family to change into members of another. There is discussion of three key categories of photochemical rearrangements involving heterocyclic compounds: Photochemical reactions involving hydrogen atom transfer (HAT), photochemical electrocyclization, and photochemical heteroatom isomerization involving heteroatoms and substituents. Heterocyclic system thermochemistry. Heterocyclic synthesis—both photoaddition and photocyclization—is quickly taking the lead as the preferred synthetic route. The processes of photochemical reactions are expounded upon in this chapter. When a molecule absorbs UV light, its energy increases to a point where bond breaking occurs. The molecule may so fragment and reorganize as a result. Based on ring size, the transformations are categorized and the impact on heterocycles is explored. There is also discussion of pyrazolines, heterocyclic dienes, and heteroaromatic compounds. In order to explore new molecular space, modern organic chemists are facing a major challenge: creating more complex and uncommon ring systems. Heterocyclic ring systems have been the subject of intense research into their biological functions. The research on organic photochemistry that has applications in organic synthesis was covered in this review. The synthesis of heterocyclic compounds was described in this review. Conventional methods are very cumbersome, expensive, or require specialist equipment that would not be useful to a synthetic organic chemist.
Keywords: Heterocycles; Photochemistry; Sixmembered rings; Ultraviolet (UV) spectroscopy Photochemical; nitrogen